2010
DOI: 10.3141/2174-09
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Uncertainty into Transportation Decision Making

Abstract: Incorporating uncertainty into transportation decision making has become a more important activity as evidenced by the popularity of scenario-based approaches in the regional transportation planning process. Particularly in decision making to promote sustainability, uncertainty and risk factors can be important elements because they can influence which alternative is perceived as the most desirable depending on a wide range of parameters. The objective of the study is to demonstrate how some of these uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Health involves the effects on the human being's physical and mental state due to accidental causes (Li et al 2012, Resendez et al 2014, long-term diseases Haupt 2007, Chow et al 2014) or exposure to sources of pollution (Jeon 2010, Yadollahi et al 2015. Community capital approach: 4 Public opinion includes the perception of the community with respect to the general acceptance of the project, unease or satisfaction with the construction or the operation of the infrastructure (Dasgupta and Edwin 2005, Gilmour et al 2011, Zavadskas et al 2015.…”
Section: Social Criteria In the Infrastructures Life Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Health involves the effects on the human being's physical and mental state due to accidental causes (Li et al 2012, Resendez et al 2014, long-term diseases Haupt 2007, Chow et al 2014) or exposure to sources of pollution (Jeon 2010, Yadollahi et al 2015. Community capital approach: 4 Public opinion includes the perception of the community with respect to the general acceptance of the project, unease or satisfaction with the construction or the operation of the infrastructure (Dasgupta and Edwin 2005, Gilmour et al 2011, Zavadskas et al 2015.…”
Section: Social Criteria In the Infrastructures Life Cyclementioning
confidence: 99%
“…In the direct allocation methods, the evaluator identifies a direct score that represents the importance of each criterion (Shen et al 2011, Koo et al 2009, Balali et al 2014). In the order relation methods, the evaluator organizes the criteria by order of importance, through which weights are obtained (Jeon 2010, Ramani et al 2011, Chen et al 2014. Some contributions consider more than one method for weight determination.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Jeon ( 7 ), uncertainty and risk factors are emphasized in the decision-making process for sustainability. An Atlanta and Georgia metropolitan region dataset is used to perform the sensitivity analysis for variation in criteria weights and sustainability evaluation results.…”
Section: Introductionmentioning
confidence: 99%
“…An Atlanta and Georgia metropolitan region dataset is used to perform the sensitivity analysis for variation in criteria weights and sustainability evaluation results. After the sensitivity analysis, it is shown that regional priorities or weights play a critical role in deciding on the preferred plan alternative, which may be superior only from the standpoint of what is considered important in that region ( 7 ).…”
Section: Introductionmentioning
confidence: 99%